Science Based Competency of Teachers in Implementing Tatanén di Bale Atikan: An Analysis based on the Asia-Pacific ESD Teacher Competency Framework - Alindra, Afridha Laily; Nuraeni, Fitri; Mustikaati, Wina; Hikmatunisa, Nenden Permas; Putri, Hafiziani Eka; Nurhafidah, Leni; Ravy, Hun (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Education for Sustainable Development (ESD) serves as a strategic framework for cultivating students’ character and ecological awareness from an early age. Primary school teachers hold a crucial role as change agents in embedding sustainability values within the learning process. This study aims to analyze elementary school teachers’ competencies in implementing ESD through the Tatanén di Bale Atikan (TdBA) approach and to examine its alignment with the Asia-Pacific ESD Teacher Competency Framework. Employing a descriptive quantitative method, data were collected using a Likert-scale questionnaire (1–5) consisting of 15 competency indicators completed by 38 teachers from various elementary schools in Purwakarta Regency. The instrument encompassed three domains: Capacity to Create Learning, Capacity to Connect through Learning, and Capacity to Continue Learning. Data were analyzed using descriptive statistics. The findings reveal that all indicators achieved an average score above 3.5, with percentage achievements ranging from 71.58% to 92.63%. Teachers demonstrated strong performance in the domains of Capacity to Create Learning and Capacity to Continue Learning. However, the Capacity to Connect through Learning domain requires further improvement, particularly in aspects of community engagement, cross-sectoral collaboration, and sustainable professional development. These findings highlight the importance of reinforcing community-based continuous professional development to ensure a more comprehensive and sustainable integration of ESD within school practicesKeywords: teacher competence, ESD, basic education, TdBA, sustainability.